Preliminary Feasibility and User Acceptance of KANA: A Digital Parent-Led Developmental Support Service in Indonesia - Marpaung, Debora; Purwanegara, Mustika Sufiati; Ashadi, Muhammad Fakhrul Rozi (Dinasti International Journal of Economics, Finance & Accounting, 2026)
This study evaluates the preliminary feasibility and user acceptance of KANA, a proposed digital parent-led developmental support concept for families of children with neurodevelopmental needs in Indonesia. Limited access to specialists, high therapy costs, and fragmented developmental guidance hinder consistent home-based intervention. This exploratory feasibility study assessed the market, service, behavioural, financial, and strategic feasibility of KANA using a descriptive mixed-method approach involving eight parents and three licensed child psychologists. Data were collected through semi-structured interviews, prototype interaction testing, a one-week real-usage trial, post-trial surveys, and secondary data analysis. Qualitative data were analysed using thematic analysis, while quantitative data were analysed descriptively using technology acceptance and behavioural readiness frameworks. Within this study's sample, the findings suggest positive user acceptance, strong market demand, favourable behavioural intention, and encouraging willingness-to-pay signals. Parents perceived KANA as useful and easy to integrate into daily routines, while expert validation supported its appropriateness as a complement to professional intervention. Overall, the findings provide preliminary evidence that KANA shows early-stage promise as a digital parent-led developmental support concept. However, the findings do not establish long-term adoption, clinical effectiveness, commercial viability, or scalability. Further staged validation involving larger and more diverse populations is required.